Summary of the National Toxicology Program benzidine dye initiative. - Morgan, D L (1994)
The benzidine dye initiative is a research program established by the National Toxicology Program to generate an integrated body of scientific information regarding the potential health risks associated with exposure to benzidine- and benzidine-congener-derived dyes. Because an in-depth evaluation of each of the hundreds of benzidine-congener-derived dyes was considered impractical, the research program was designed to study the metabolism and disposition, genetic toxicity, and in vivo toxicity and carcinogenicity of two primary benzidine congeners, 3,3'-dimethylbenzidine and 3,3'-dimethoxybenzidine, and a select group of prototypical dyes derived from those amines. It was anticipated that by applying the basic information generated in these extensive studies, it would be possible to make regulatory decisions about other dyes after conducting only a minimal number of experiments such as studies of disposition and metabolism, and in vitro mutagenicity. This paper summarizes the results of studies conducted to evaluate the metabolism, disposition, mutagenicity, toxicity, and carcinogenicity of representative benzidine congeners and derived dyes.